2016
DOI: 10.1161/jaha.116.003323
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Low‐Density Lipoprotein Cholesterol, Free Proprotein Convertase Subtilisin/Kexin Type 9, and Alirocumab Levels After Different Lipid‐Lowering Strategies

Abstract: BackgroundAlirocumab undergoes target‐mediated clearance via binding of proprotein convertase subtilisin/kexin type 9 (PCSK9). Statins increase PCSK9 levels; the effects of nonstatin lipid‐lowering therapies are unclear. Every‐4‐weeks dosing of alirocumab may be appropriate for some patients in absence of background statin but is not yet approved.Methods and ResultsLow‐density lipoprotein cholesterol (LDL‐C), PCSK9, and alirocumab levels were assessed in subjects (LDL‐C >130 mg/dL, n=24/group) after a 4‐week r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 17 publications
8
35
0
Order By: Relevance
“…In line with previous studies,17, 18 alirocumab 150Q4W (and 75Q2W) led to a rapid and robust reduction in mean free PCSK9 levels, which persisted for at least 3 weeks (as shown between weeks 9 and 11) following alirocumab 150Q4W administration. With administration of alirocumab 75Q2W, mean free PCSK9 levels remained below 25% of baseline levels throughout the 4‐week period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous studies,17, 18 alirocumab 150Q4W (and 75Q2W) led to a rapid and robust reduction in mean free PCSK9 levels, which persisted for at least 3 weeks (as shown between weeks 9 and 11) following alirocumab 150Q4W administration. With administration of alirocumab 75Q2W, mean free PCSK9 levels remained below 25% of baseline levels throughout the 4‐week period.…”
Section: Discussionsupporting
confidence: 91%
“…Alirocumab 150 mg Q4W monotherapy demonstrated a 47.4% reduction in LDL‐C levels from baseline in a phase 1 study 17. However, in an early phase 2 study of patients with heterozygous familial hypercholesterolemia on statin, there was only an incremental LDL‐C reduction of 28.9% at week 12 with alirocumab 150 Q4W 18.…”
Section: Introductionmentioning
confidence: 99%
“…Background statin seems to have more of an impact on alirocumab efficacy when longer dosing intervals are used (every 4 weeks [Q4W] vs Q2W). Phase 2 studies indicated that efficacy was not fully maintained over the dosing interval when alirocumab 150 mg Q4W was co-administered with a statin2122, probably because of statin-induced increases in PCSK9 levels leading to increased alirocumab clearance19. However, efficacy was stable with the 150 mg Q2W dose when co-administered with a statin2122, and has also been shown to be relatively stable with a dose of 300 mg Q4W23.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, higher PCSK9 concentrations through increased PCSK9 production are thought to increase the clearance of alirocumab19. Statin therapy increases circulating levels of PCSK9 through the statin-mediated activation of the transcription factor sterol regulatory element-binding protein-2, which leads not only to increased expression of the LDLR gene but also of the PCSK9 gene920.…”
mentioning
confidence: 99%
See 1 more Smart Citation